2016
DOI: 10.1259/bjr.20151022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of dual-energy spectral imaging with adaptive statistical iterative reconstruction for reducing contrast medium dose in CT portal venography: in comparison with standard 120-kVp imaging protocol

Abstract: Objective: To evaluate the clinical value of dual-energy spectral CT with adaptive statistical iterative reconstruction (ASiR) for reducing contrast medium dose in CT portal venography (CTPV). Methods: This prospective study was institutional review board-approved, and written informed consent was obtained from all patients. 50 patients undergoing abdominal CT were randomized to 2 groups: Group A (n 5 25), using spectral CT and 350 mgI kg 21 contrast injection protocol; Group B (n 5 25), using standard 120 kVp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that the spatial resolution and image noise could be balanced at approximately 40% -50% ASiR (maintain image spatial resolution while reducing noise) (32). We selected the 50% ASiR weights used by other researchers in abdominal low-dose CT scans (33) and portal vein imaging studies (34,35). This was also the most commonly used weight in CM passes through the superior vena cava into the right heart and then goes directly to the branches of the pulmonary artery from the right heart without systemic circulation in CTPA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the spatial resolution and image noise could be balanced at approximately 40% -50% ASiR (maintain image spatial resolution while reducing noise) (32). We selected the 50% ASiR weights used by other researchers in abdominal low-dose CT scans (33) and portal vein imaging studies (34,35). This was also the most commonly used weight in CM passes through the superior vena cava into the right heart and then goes directly to the branches of the pulmonary artery from the right heart without systemic circulation in CTPA.…”
Section: Discussionmentioning
confidence: 99%
“…As the penetration of X-ray reduces with increase in the patients' body mass index ( 24 ), it has been hypothesized that the image quality in lower tube voltage may be affected in patients with higher body mass index. In case of patients with a high body mass index, the optimal CNR spectroscopy technology can provide higher quality images of the abdominal blood vessels and portal veins with the application of low dosage of contrast agent for reducing the total iodine content ( 25 26 ). In imaging patients with greater body mass indexes, the use of energy spectrum plus adaptive statistical iterative reconstruction algorithm can provide abdominal vascular images of good quality without increasing X-ray radiation and contrast dosage compared with traditional angiography ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the current state-of-the-art CT scanners provide multi-kVe spectral imaging capability or enable low kVp imaging without increasing image noise using iterative reconstruction. These scanners allow for augmented contrast enhancement relative to conventional CT for a given amount of contrast medium ( 15 16 17 18 19 20 21 22 23 24 ). As these scanners decrease the amount of contrast agent needed, injection flow rate and need for large intravenous catheters can be reduced.…”
Section: Discussionmentioning
confidence: 99%